Faktor-Faktor yang Mempengaruhi Disiplin Kerja Karyawan Penunjang Medis dan Non Medis - Muhammad Amin; Septi Puspita Sari; Abdul Rachman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the factors related to the work discipline of medical and non-medical support employees of the Soeprapto Mental Hospital, Bengkulu Province in 2017. This type of research is a quantitative study with a cross sectional research design. The results of statistical tests show that the relationship between exemplary leadership and work discipline p-value 0.016, the relationship between remuneration for work discipline p-value 0,000, the relationship between penalties for work discipline with a p-value of 0.009 while job objectives p-value of 0.390 and ability employees with a p-value of 0.375. In conclusion, there is a significant relationship between exemplary leaders, remuneration and penalties for work discipline. There is no significant relationship between job goals and employee abilities with the work discipline of medical and non-medical support employees at Soeprapto Mental Hospital, Bengkulu Province. Keywords: Remuneration, Work Discipline, Exemplary Leaders, Punishment Sanctions